Determining factors of social entrepreneurial intentions of desa mandiri budaya in yogyakarta - Kurniawati, Lucia; Rubiyatno, Rubiyatno; Diva V.W, Maria Angela (Enrichment : Journal of Management, 2023)
Desa Mandiri Budaya consists of a Cultural Village, Tourism Village, Prima Village and Preneur Village. The four components of Desa Mandiri Budaya must work well together. The community involved in these components must have a high spirit of social entrepreneurship. This research uses social entrepreneurship intentions through the Theory of Planned Behavior. Therefore, this study aims to determine the antecedents of social entrepreneurship intentions, namely subjective norms, attitudes towards social entrepreneurship and perceived behavior control. The focus of this research is 7 Desa Mandiri Budaya in the Special Region of Yogyakarta. This research is quantitative research. Data gathering strategies using surveys include self-administered, self-managed surveys sent via questionnaires. Non-probability sampling with the incidental sampling approach was employed. Regression analysis was the nonparametric statistical test employed in this investigation. During the early stages of testing and data processing, instrument testing included validity and reliability tests, as well as traditional assumption tests. Models and hypotheses are tested using Test F and Test t. The other factors were influenced by variables not explored in this study. As a result, perceived behavioral control, attitude toward becoming a social entrepreneur, and subjective norms are all significantly associated with the intention to engage in social entrepreneurship; subjective norms influence social entrepreneurial intention; attitude toward becoming a social entrepreneur has no influence on social entrepreneurial intention; and perceived behavioral control influences social entrepreneurial intention. The findings should give recommendations for Desa Mandiri Budaya.